Analysing olfactory and auditory sensescapes in English cities: Sensory expectation and urban environmental perception - Neil Bruce; Jenna Condie; Victoria Henshaw; Sarah R. Payne (Ambiances)
This paper examines the role of sensory expectation in people’s experiences and perceptions of a range of different urban environments in English towns and cities by focussing upon those related to smell and sound specifically. It draws from two separate but related sensewalking studies undertaken between 2004 and 2009: one exploring urban smell experiences, the other examining urban sound experiences. In drawing from, and comparing the findings of these two studies, sensory expectations are argued as highly influential in urban place experience and perception, providing different layers of meaning and understanding of place, and presenting challenges and opportunities for architects and urban designers when creating more human-centred places in the city. In addition, perceptions of the smells and sounds themselves are revealed as highly influenced by the environmental context within which they are, or are not, detected. As a result, the authors advocate a more proactive approach to the consideration of smells and sound information when designing and managing urban sensory environments.